HUBUNGAN ANTARA SELF-COMPASSION DENGAN STRES AKADEMIK PADA REMAJA SMA DI DENPASAR - Putu Tezya Arisantika; I G A A Yunita Utami; Lidia Sandra (CV. Lafadz Jaya, 2026)
This study aimed to examine the relationship between self-compassion and academic stress among senior high school adolescents in Denpasar. Academic stress is a prevalent psychological issue among adolescents due to increasing academic demands and pressures. Self-compassion is conceptualized as a psychological resource that enables individuals to respond to difficulties more adaptively through self-kindness, self-acceptance, and healthy emotional regulation. This study employed a quantitative correlational design involving 401 senior high school adolescents in Denpasar selected through a predetermined sampling technique. Data were collected using the Self-Compassion Scale and the Academic Stress Scale. Spearman’s Rho correlation analysis was conducted because the data were not normally distributed. The findings revealed a significant negative correlation between self-compassion and academic stress (ρ = −0.274; p < 0.05), indicating that higher levels of self-compassion are associated with lower levels of academic stress. These results suggest that self-compassion functions as a protective factor in reducing academic stress among senior high school adolescents in Denpasar